Strategies for Training Technical and Non-technical Surgical Skills. (September 2013) - Miller, A.; Sun, T.; Pyatka, N.; Brewer, J.; Ganapathy, S.; Weyhrauch, P.; Niehaus, J.; Cao, C.G.L.
Even though laparoscopic surgery has become the preferred technique for many surgeons, the methods of training are not standardized. Most simulators and training programs focus on training technical skills, neglecting very important non-technical skills. This study examined the benefits of different strategies of training both technical and non-technical skills amongst different experience levels. Twenty-seven subjects participated in the study (9 novices, 9 intermediate experience level subjects, and 9 advanced subjects). They were divided into 3 groups: technical, non-technical, and combined. Subjects practiced a purely technical, purely non-technical, and a combined technical and non-technical simulated surgical task. Data from pre-test and post-test scores as well as the last training block of combined training were analyzed for time to completion, number of technical errors and number of non-technical errors. Results suggest that there may be a benefit to training non-technical skills alone first, or in conjunction with technical surgical skills in novices during the beginning phases of learning.